Re-cognizing Co-management as Co-governance: Visions and Histories of Conservation at James Bay - Feit, Harvey A. (Anthropologica, 2022)
James Bay Cree "hunting leaders" claim extensive authority over their hunting territories, including authority to control non-Native activities on them. They are encouraged by recalling that their authority has been recognized repeatedly by government officials over decades. I show that beaver conservation and co-management included repeated acknowledgments that nation state and Cree governing practices co-existed and were necessary to each other. I examine how recognition of co-governance can be an "effect" of co-management. But co-governance is a governmentality whose logic is outside the claims of nation states to exclusive sovereignty, and therefore its practice is acknowledged ambiguously and inconsistently.